Wealth accumulation and retirement preparedness in cross-national perspective: A gendered analysis of outcomes among single adults - Janet C. Gornick; Eva Sierminska (Institute of Labor Economics (IZA), 2021)
Wealth is an increasingly important dimension of economic well-being and is attracting rising attention in discussions of social inequality. In this paper, we compare - within and across countries - wealth outcomes, and link those to both employment-related factors and policy solutions that have the potential to improve wealth creation and retirement security for women. By constructing country-specific portraits of wealth outcomes and "retirement preparedness," we reveal extensive cross-national variation in multiple facets of wealth. Our regression analysis finds a statistically significant and positive effect of work experience on wealth, with that effect, in general, increasing over time. The effect of work experience for single women is greater than for single men, suggesting that, among men, other, stronger forces are at work in creating wealth. The retirement preparedness outcomes indicate that single women in all three countries are in a precarious position at retirement, with much lower expected annual wealth levels than single men. The second preparedness indicator, which links expected annual wealth to income, demonstrates that men have the potential to cover 1larger shares of their income at retirement - and thus are more able, than their female counterparts, to maintain standards of living achieved earlier in life. Our policy discussion indicates that employment remains a viable option for ultimately bolstering women's wealth accumulation. Many scholars, gender equality advocates, and policymakers have argued for raising women's employment rates - for a multitude of reasons - but few, if any, have made the case for strengthening women's employment in order to ultimately bolster women's wealth building. We hope to help reduce the gap in the literature on policy supports for women's employment and re-open the discussion on how women can create more wealth.
Keywords: J10; J16; I38; 330; wealth; gender; labor market